Application of “SISBAR” for effective communication between nurses and doctors at private hospital in Indonesia. - Asep Badrujamaludin; Dedi Supriadi; Oktovina Yesayas; Fauziah Rudhiati; Hemi Fitriani; Tria Firza Kumala; Sri Wahyuna (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Aims : Effective communication is the main elements of patient safety goals because communication is the first cause of patient safety problems. Effective communication must be built on aspects of clarity, accuracy, in accordance with the context of language and information, systematic flow, and culture. This study looks at whether there is an effect of SISBAR communication than SBAR on effective communication between nurses and doctors during consultations or handovers Design : Observational study to 20 nurses as Nurse incharge at Ruby Barat and Timur in SHBC (Santosa Hospital Bandung Central), with Observational Chart of SISBAR in 1 month observation. Methods : This research method uses a quasi-experimental pre and post by using an observational study.  The statistical analysis test using the Wilcoxon non-parametric test. Results : The results of the statistical analysis test using the Wilcoxon non-parametric test obtained p-Value: 0.002 (< 0.05), meaning that there was an significant effect of SISBAR communication on effective communication than SBAR between nurses and doctors in SHBC Bandung. Conclusions : The results of this study indicate that SISBAR communication is more effective to be applied than SBAR. In SBAR even though there is an element of the introduction, but because it is not mentioned in the abbreviation, nurses often forget about the introduction (aspects of introducing themselves and who is speaking). Therefore, SISBAR can be an alternative in handover communication between nurses and doctors in hospitals. SISBAR communication with the development of SBAR, ISBAR to SISBAR can be developed in others hospitals and in Indonesia generally